Repeated Changes in Reported Sexual Orientation Identity Linked to Substance Use Behaviors in Youth - Ott, Miles Q. (2012)
PURPOSE: Previous studies have found that sexual minority (e.g., lesbian, gay, bisexual) adolescents are at higher risk of substance use than heterosexuals, but few have examined how changes in sexual orientation over time may relate to substance use. We examined the associations between change in sexual orientation identity and marijuana use, tobacco use, and binge drinking in U.S. youth. METHODS: Prospective data from 10,515 U.S. youth ages 12-27 years in a longitudinal cohort study were analyzed using sexual orientation identity mobility measure M (frequency of change from 0 [no change] to 1 [change at every wave]) in up to five waves of data. Generalized estimating equations were used to estimate substance use risk ratios and 95% confidence intervals; interactions by sex and age group were assessed. RESULTS: All substance use behaviors varied significantly by sexual orientation. Sexual minorities were at higher risk for all outcomes, excluding binge drinking in males, and mobility score was positively associated with substance use in most cases (p<.05). The association between mobility and substance use remained significant after adjusting for current sexual orientation and varied by sex and age for selected substance use behaviors. This association had a higher positive magnitude in females than males and in adolescents than young adults. CONCLUSIONS: In both clinical and research settings it is important to assess history of sexual orientation changes. Changes in reported sexual orientation over time may be as important as current sexual orientation for understanding adolescent substance use risk.